Effects of water boiling, microwave, and water bath post-polymerization on mechanical properties of acrylic denture resins - Kostić Milena; Nikolić Ljubiša; Nikolić Vesna; Petković Dušan; Igić Marko; Krunić Nebojša; Manić Miodrag; Gligorijević Nikola; Radenković Goran (Hemijska Industrija, 2018)
Acrylic restorations in the mouth are exposed to strong occlusal forces. Their mechanical properties depend on the type and method of their polymerization. The aim of this study is a comparative analysis of mechanical properties (flexural strength and modulus of elasticity) of acrylic materials before and after the post-polymerization treatments (water boiling, microwave irradiation and water storage). The study included denture base resins, as well as an acrylate for orthodontic appliances impregnated with aesthetic beads. Flexural strength, modulus of elasticity and the deflection were measured immediately after polymerization, after a hot and microwave post-polymerization and after immersion in a water bath at the temperature of 37°C. The applied post-polymerization methods resulted in an increase in flexural strength and modulus of elasticity relative to the initial values for all tested materials. Being aware of the reduction in fracture risk of dental prosthesis after a proposed post-polymerization procedure, it could be used in all clinical situations where there is an increased risk of damage to dentures.